A study on the career advancement of graduates of Master of Management (MM) course at the University of the Philippines Visayas (UPV) employed in Government Owned and Controlled Corporation (GOCC) offices and Government Finance Institutions *GFIs) in Iloilo City
Objectives of the study : A) To assess and evaluate the scope, extent and breadth of the contribution of having Master of Management Degree earned in UPV to the career advancement of employees. B) Specific : 1) To determine if the personal circumstances of an employee with MM degree from UPV significantly affect or influenced their career advancement in government service and banking institutions. 2) To examine if having an MM degree earned in UPV affect the performance of employees in the government service and in banking institutions. 3) To evaluate the chances of employees who have earned an MM degree in UPV be promoted in their office or institution. 4) To determine if having an MM degree earned in UPV afford/improve the influence and popularity of employees over his/her co-employees. C) Scope and coverage: The study focused on the career advancement of MM graduates of UPV who at the time they graduate were already working in GOCC's and GFI's in Iloilo City. The study is purely limited only to the survey of employees who are graduates of MM Degree from UPV from the year 1990-1998 and who are employed or working in the GOCCs offices stationed or based in Iloilo City. The respondents were those working already in a particular GOCC or GFI before and after he/she obtained an MM Degree. The study did not include those MM Graduates who were not employed yet with any of the GOCC and GFI Offices at the time they earned their masteral degree. D) Methodology: Data gathering started in July 2001 using the structured questionnaires. In the analysis of data, totals, percentages and means were used. E) Major findings: The respondents profile reveal that majority of MM Graduates are female, married and between 25-40 years old. Results of the study reveals that majority of those taking the Master of Management Degree are graduates of the Bachelor of Science in accounting and most of them took up Master in Business Management. Most of the respondents who are able to finish the MM degree for a minimum of two (2) years have similar purpose, that is, obtaining the degree for career advancement. F) The researchers have found out that although having an MM degree does not contribute to the career advancement of the respondents their performance, opinions and outlook/perception was significantly affected. As a consequence, they gain more self confidence and respect for themselves and others. They became more prudent in decision making. G) Recommendations: It is recommended by the researchers that a more thorough and in depth study of the subject should be made in order to further validate the study. And it is more recommended that a more comprehensive coverage of the respondents especially in other cities, towns or regions.